Rhizosphere Bacteria Plumeria acuminata Increases Growth of Zea mays After Root Inoculation - Insani, Qori Tsaniyah Ainun; Rahayu, Triastuti; Widianto, Donny; Listiawati, Vina; Mumpuni, Kistantia Elok; Prayitno, Trio Ageng; Sidiq*, Yasir (Jurnal IPA & Pembelajaran IPA, 2023)
The bacteria found in the rhizosphere are called plant growth promoting rhizobacteria (PGPR), namely bacteria that can stimulate plant growth by producing growth hormones, one of which is the hormone indole acetic acid (IAA) which plays a role in regulating plant growth and development. Five isolates of rhizosphere bacteria were isolated on frangipani roots (P26, P31, P36, P37 and P38). Previous research showed that five bacterial isolates were capable of producing the hormone IAA. However, evidence of its potential as a PGPR has not been obtained. Therefore, the aim of this study was to test the effect of inoculation of rhizosphere bacteria on maize plants. The research method uses a quantitative experimental method, namely 15 repetitions for each treatment. Data collection was carried out 1 day after planting (HTS) until the 14th day. Data were analyzed using a 95% confidence student t-test or with a significance level of 5% (a=0.05). This inoculation begins with germinating maize seeds and observing the roots. The germinated maize seeds are then soaked in the bacterial suspension for one hour at room temperature. The results showed that inoculation with isolates P36, P37 and P38 significantly increased the height of maize plants, while isolate P37 significantly increased the number of leaves and root length of corn plants, isolate P38 could significantly increase the number of roots of corn plants.Thus, these results support the evidence that rhizosphere bacteria from frangipani have an effect on increasing the growth of maize plants